Pengaruh Pemberian berbagai Konsentrasi POC terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq) pada Pembibitan Utama - Hardiyanti, Lidya Sri; Desi, Yulfi; Novia, Prima (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2023)
Oil palm (Elaeis guinensis Jacq) is a plantation crop that plays an important role for Indonesia as a mainstay commodity for export and as a commodity that is expected to increase farmers' income. Currently, Indonesia is the largest producer of crude palm oil (CPO) in the world. The research was conducted from March - July 2018. The aim of the research was to obtain the best POC concentration for the growth of oil palm (Elaeis guineensis Jacq) seedlings. The research was in the form of an experiment using a Completely Randomized Design (CRD) with 5 treatments and 5 replications, so there were 25 experimental units. As treatments are various concentrations of POC, namely: 0.20%, 40%, 60%, 80%. The data for each observation of oil palm seeds obtained was analyzed using the Duncant's New Multiple Range Test (DNMRT) at a significance level of 5%.